Contradictions in The Implementation of The Death Crime in Indonesia: Fiqhi Jinayah's Perspective And Legal Renewal Policy National Crime - Marlina, Andi; Mohammad Hazyar Arumbinang; Donny Eddy Sam Karauwan (DIKTUM: Jurnal Syariah dan Hukum, 2023)
This study aims to scrutinize the contradictions inherent in the application of the death penalty from two distinct perspectives: the perspective of Islamic criminal law (jinayah) and the ongoing reforms in Indonesian criminal law. In Islamic criminal law, the purpose of the death penalty lies in safeguarding religion, the soul, the mind, lineage, and property. The study utilizes a qualitative approach to analyze legal sources and relevant literature, aiming to provide a comprehensive understanding of the contentious nature of the death penalty in Indonesia. The findings highlight the ongoing complexity and controversy surrounding the death penalty in Indonesia, encompassing various legal, ethical, and human rights perspectives. The text underscores the multifaceted nature of the debate, emphasizing the need for careful consideration of international standards, societal norms, and legal frameworks in shaping policies related to capital punishment. The findings contribute to the broader discourse on human rights, legal reform, and the ethical considerations surrounding the death penalty..